Outcomes of Surgery followed by Local Brain Radiotherapy Compared with Surgery followed by Whole Brain Radiotherapy for Single Brain Metastasis. Issue 4 (July 2017) - Igaki, Hiroshi; Harada, Ken; Umezawa, Rei; Miyakita, Yasuji; Ohno, Makoto; Takahashi, Masamichi; Sumi, Minako; Inaba, Koji; Murakami, Naoya; Ito, Yoshinori; Narita, Yoshitaka; Itami, Jun
Purpose: To determine the clinical efficacy of surgery followed by local brain radiotherapy (LBRT) for patients with a single brain metastasis, by comparing the results with those of postoperative whole brain radiotherapy (WBRT). Methods: We performed a retrospective analysis to compare the survival rate, recurrence-free rates, and causes of death for single brain metastasis patients who underwent surgery followed by LBRT or WBRT in the 2010-2015 period. Results: After their surgery, 22 and 32 patients were treated by LBRT and WBRT, respectively. The median survival times for these LBRT and WBRT groups were 18.3 months and 19.2 months, respectively (p = 0.356). The local recurrence-free rates were 81.2% at 1 year and 81.2% at 2 years after LBRT, and 63.8% at 1 year and 58.9% at 2 years after WBRT (p = 0.589). The distant brain recurrence-free rates were 42.5% at 1 year and 25.5% at 2 years after LBRT, and 69.8% at 1 year and 52.4% at 2 years after WBRT (p = 0.044). Distant brain recurrences were observed significantly more frequently in the LBRT group, but the rates of salvage treatment application and survival were not significantly different between the LBRT and WBRT groups. The probability of neurologic death was not significantly higher in the LBRT group compared with the WBRT group. Conclusions: Surgery followed by LBRT for single brain metastasis is not inferior to postoperative WBRT, because survival and the necessity of salvage treatment after LBRT were equivalent to those after WBRT.